Analysis of Money Supply and Demand on Economic Growth in Five Emerging Market Countries - Fitri Annisa; Dewi Mahrani Rangkuty (Cattleya Darmaya Fortuna, 2026)
Demand and supply are two fundamental elements in an economic system that are interrelated and determine market equilibrium. Both play an important role in regulating prices, the quantity of goods, and services circulating in society. In the context of a modern economy, changes in either demand or supply can have significant impacts on national economic stability. This study aims to analyze the effect of money demand and money supply on economic growth in the short term, medium term, and long term in five emerging market countries. This research employs a quantitative approach, focusing on five emerging market countries, namely Indonesia, Malaysia, Thailand, China, and Brazil, using secondary data obtained from the World Bank over the period 2005 to 2024. The method used in this study is Vector Autoregression (VAR). The results indicate that money demand and money supply have an influence on economic growth in emerging market countries. In the medium term, inflation and interest rates play a central role as instruments that respond to economic growth dynamics. Interest rates function as a tool to control the demand and supply of money in a country, while inflation can affect economic growth, particularly when demand exceeds supply capacity.